Solving the Expression (6) + (6)  2  (5) * (1)  2(4  2)
This expression involves several operations, so we need to follow the order of operations (PEMDAS/BODMAS) to solve it correctly.
PEMDAS/BODMAS stands for:
 Parentheses ( Brackets)
 Exponents ( Orders)
 Multiplication and Division (from left to right)
 Addition and Subtraction (from left to right)
Let's break down the expression stepbystep:

Parentheses/Brackets:
 (4  2) = 2

Multiplication:
 (5) * (1) = 5
 2 * 2 = 4

Addition and Subtraction (from left to right):
 (6) + (6) = 12
 12  2 = 14
 14  5 = 19
 19  4 = 23
Therefore, the solution to the expression (6) + (6)  2  (5) * (1)  2(4  2) is 23.